Benchmarking of Cph1 Mutants and DrBphP for Light‐Responsive Phytochrome‐Based Hydrogels with Reversibly Adjustable Mechanical Properties. Issue 7 (28th April 2022) - Emig, Ramona; Hoess, Philipp; Cai, Hanyang; Kohl, Peter; Peyronnet, Rémi; Weber, Wilfried; Hörner, Maximilian
Abstract: In the rapidly expanding field of molecular optogenetics, the performance of the engineered systems relies on the switching properties of the underlying genetically encoded photoreceptors. In this study, the bacterial phytochromes Cph1 and Dr BphP are engineered, recombinantly produced in Escherichia coli, and characterized regarding their switching properties in order to synthesize biohybrid hydrogels with increased light‐responsive stiffness modulations. The R472A mutant of the cyanobacterial phytochrome 1 (Cph1) is identified to confer the phytochrome‐based hydrogels with an increased dynamic range for the storage modulus but a different light‐response for the loss modulus compared to the original Cph1‐based hydrogel. Stiffness measurements of human atrial fibroblasts grown on these hydrogels suggest that differences in the loss modulus at comparable changes in the storage modulus affect cell stiffness and thus underline the importance of matrix viscoelasticity on cellular mechanotransduction. The hydrogels presented here are of interest for analyzing how mammalian cells respond to dynamic viscoelastic cues. Moreover, the Cph1‐R472A mutant, as well as the benchmarking of the other phytochrome variants, are expected to foster the development and performance of future optogenetic systems. Abstract : Phytochromes are among the most important photoswitches in molecular optogenetics. In this study, different bacterial phytochrome variants are benchmarked for their suitability as molecular switches in light‐responsive biohybrid hydrogels with reversibly adjustable mechanical properties. A variant of the cyanobacterial phytochrome 1 (Cph1) is identified that confers the Cph1‐based hydrogel with an increased dynamic range of the storage modulus.